Anti-inflammatory alkaloid glycoside and quinoline alkaloid derivates from the stems of Clausena lansium1. Issue 98 (23rd October 2015) - Liu, Jie; Li, Chuang-Jun; Ni, Lin; Yang, Jing-Zhi; Li, Li; Zang, Cai-xia; Bao, Xiu-Qi; Zhang, Dan; Zhang, Dong-Ming
<x xml:space="preserve">Abstract</x> Six new alkaloid glycosides (1–6), along with two new quinoline alkaloids (7–8), were obtained from the stems of Clausena lansium. Compounds 4, 6, 9, 17 and 18 showed moderate inhibitory effects on LPS-induced NO production in murine microglial BV2 cells.